Exosome‐based targeted RNA delivery for immune tolerance induction in skin transplantation. Issue 7 (20th March 2020) - Li, Chunmin; Guo, Fengjie; Wang, Xueli; Liu, Dongxu; Wu, Bolun; Wang, Fenghua; Chen, Wen
Abstract: Exosomes have been widely applied to the delivery of RNA and small molecules currently. However, the low targeting and specificity greatly limited the effect of exosome delivery. Here we designed an exosome that can perform the targeted delivery of two different types of RNA. Based on the mesenchymal stem cells (MSCs) derived exosomes, the RNA delivery system of targeted dendritic cells (DC‐Exosome) was constructed, using the layer by layer self‐assembly. DC‐Exosomes can specifically bind to DCs, while guiding the endocytosis of chimeras and exosome. Then aptamer/siRNA chimera was cut into mTOR siRNA by Dicer, and microRNA was released from exosome under lysosomal digestion. SIGN aptamer performed the rapid induction of immune tolerance, and later mTOR siRNA was formed to inhibit mTOR pathway and suppress immune responses. Exosomes could maintain long time‐stability after PEG‐PEI polyplexes modification and promote HLA‐G expression in DCs continuously. Animal experiments showed that DC‐Exosomes could induce immune tolerance at 3, 7, and 14 days after skin transplantation. Compared with the microRNA‐Exosome group, the number of CD11c+ DCs in DC‐Exosome group decreased, while the proportion of HLA‐G+ DCs increased remarkably. In conclusion, we constructed a new exosome‐based targeted delivery system which could effectively induce the immune tolerance in transplantation.